A 2020 Update on 20/20 X 2 Diplopia after Ocular Surgery: Strabismus Following Retinal Detachment Surgery. Issue 4 (2nd October 2021) - Velez, Federico G.
ABSTRACT: Persistent ocular motility and sensorial abnormalities following retinal detachment surgery are not common. Scleral buckling increases the risk of deviation in secondary gaze positions most commonly horizontal deviations. Suspect superior oblique incarceration in patients with limited downgaze. For patients with persistent strabismus, surgery is an option. Removing the exoplant may be necessary to access the extraocular muscles but the effect on alignment is minimal except in cases were the scleral buckle migrates anteriorly causing restriction. Removing the scleral buckle may increase the risk of retinal re-detachment. Hangback recessions and adjustable sutures can be safely used.